GEOHERITAGE POTENTIAL AS GEOTOURISM SPOT BASED ON QUANTITATIVE AND QUALITATIVE ANALYSIS IN BANDUNG, WEST JAVA - Hana Nur Aini; Hilfi Taufiqul Rahman; Achmad Djunarma Wirakusumah; Rachmat Heryadi (International Journal of Geotourism Science and Development, 2021)
Bandung is one of area with abundant geodiversity which also indicates high geotourism potential. One of Bandung geodiversity attractive aspect is the high scientific value related to Tectono-Volcanic History of Bandung which have a good Geoheritage potential. This research intends to assess the Geoheritage potential for Geotourism purposes in Ban-dung City. Research methods such as field observation, literature study, quantitative and qualitative analysis aimed toward at seven geoheritage potentials: Sunda Ignimbrite at Goa Jepang, Sunda Ignimbrite at Goa Belanda, Lava Tube at Cikapundung River, Pahoehoe Lava at Cikapundung River, Ropy Lava at Curug Lalay, Columnar Joint Lava at Curug Omas and Lembang Fault Scarp at Keraton Cliff. Quantita-tive Analysis is based on classification for geotourism pur-poses which includes Intrinsic and Scientific Value, Educa-tional Value, Economic Value, Conservation Value, etc. Quantitative analysis indicates that Geoheritages in Bandung City have a good potential for Geotourism purposes with mean percentage score of >59%.